Identification and characterization of a rabbit novel IFN-α unlocated in genome. (January 2018) - Gao, Mingchun; Liu, Ying; Guo, Yongli; Wang, Yujiao; Dai, Haiyue; Song, Zhifeng; Wang, Junwei; Han, Wenyu
Abstract: The multigene family of rabbit IFN-α (RbIFN-α) is located on chromosome 1, which shows seven functional genes in type I IFN locus. A novel RbIFN-α that remains unlocated in the rabbit genome was amplified and designated as the first novel rabbit IFN-α (RbIFN-αNov1), which possesses the typical molecular characteristics of type I IFNs and could be induced in RK-13 cells and peripheral blood mononuclear cells. After the mature peptide of RbIFN-αNov1 was expressed, its antiviral activity, physicochemical characteristics, and cytotoxicity were determined in vitro. Results indicated that RbIFN-αNov1 exerted a high specific antiviral activity against VSV and a low cytotoxic effect on RK-13 cells. RbIFN-αNov1 showed high sensitivity to trypsin and remained relatively stable after acid, alkali, or heat treatment. RbIFN-αNov1 could induce Mx1 expression on RK-13 cells and activate the NF-κB, ISRE and BoIFN-β promoter activities on bovine testicular cells. Overall, our research on RbIFN-αNov1 not only enriches the knowledge about rabbit IFNs but also makes RbIFN-αNov1 have the potential to be used as an effective therapeutic agent for rabbit viral diseases. Highlights: Rabbit type I interferon locus was constructed and analyzed. An unlocated rabbit IFN-α designated as RbIFN-αNov1 was characterized. RbIFN-αNov1 has broad antiviral activity and antiproliferative activity. RbIFN-αNov1 can induce Mx1 expression to exert antiviral activity. RbIFN-αNov1 can induce NF-κB, ISRE and BoIFNβ promotor activity on BT cells.